O ensino de História da Educação na Escola Normal Nossa Senhora das Dores em Uberaba, Minas Gerais, Brasil (1928-1971) - Silva, Marlon César (2024)
This doctoral thesis is inserted in the Education area, sub-area of the History of Education subject on the Disciplinary History theme. It is focused on the teaching of the History of Education subject in the Teacher Training Course at Nossa Senhora das Dores School, a religious school managed by Dominican nuns in Uberaba-MG from 1928 to 1971. It is an attempt to understand the dynamics of the development of the subject, the mishaps, the transience and the designs and redesigns of this subject during this period. The year 1928 was the starting point of the introduction of the History of Education subject into the curriculum of Nossa Senhora das Dores School and it ended in 1971 when deep reforms in educational legislation took place. The general objective was to understand how the subject of History of Education was taught at this school, which corresponded to the Teacher Training Schools of the State of Minas Gerais and compared to the Model School of Teacher Training in the capital. The curricular changes made, the teaching practices used, the methodology and the laws and rules were studied. Beyond the processes, changes and efemerity present in the designs and redesigns of the subject, we searched for teaching materials such as content manuals, records of former students and teachers such as notebooks and class diaries as well as interviews. We worked with the purpose of identifying the nuances present in the dynamics in which the practice of the teaching of the History of Education subject took place. As for theoretical support we counted mainly on Lopes (1986), Chervel (1990) Melo (2002), Gatti Jr. (2008) and Guimarães (2012 e 2016). The results of this research were presented in three chapters: 1) The foundation of Nossa Senhora das Dores School and the introduction of the History of Education subject; 2)The prescriptions for the teaching of the History of Education subject in Teacher Training Schools: the teaching programs and manuals; 3) The memories of former teachers and students on the teaching of History Education in Nossa Senhora das Dores School. We came to the conclusion that the teaching of the History of Education subject was present in the teacher training program of this institution and it was revealed that for some periods it was integrated with other subjects such as Philosophy of Education, History of Civilization or even Pedagogy and Hygiene.